METHODOLOGY OF MODELLING: SIMULATION OF URBAN SCENARIOS - Riegel, Roberta Plangg; Alves, Darlan Daniel; Birlem, Leonardo Espíndola; Schmidt, Bruna; Rodrigues, Marco Antônio Siqueira; Quevedo, Daniela Muller de (Revista Conhecimento Online: Diversidade e Inclusão Social, 2019)
ABSTRACT Urbanization has led to a series of problems in medium and large cities, resulting from a lack of planning and technologies to support decision making. This work aims to contribute to the methodology of modeling by cellular automata, aiming the study of the processes that condition the expansion of the urban area. Having as a study case of the municipality of Novo Hamburgo, RS, Brazil. For this purpose, the urban areas of 1967, 1977, 1987, 1997, 2009 and 2015 were used, totalling a historical analysis of 48 years, besides the thematic maps: Declivities, Hypsometric, Land Use, Water Resources and Road System. The compiled data was inserted in the environment of the platform Dinamica EGO, which is a free software that uses the system of Cellular Automata. The software employs a set of input maps composed of an initial landscape, a final landscape and a compilation of thematic variables that are combined from the definition of weights of evidence to generate the transition probability maps. The results showed similarity indexes of 0.9 for the first three models, 1977, 1987 and 1997, as well as 0.83 for the simulation of 2015. It was also possible to analyze the predominant factors for each expansion process, besides the simulation of areas of prognosis for short and medium term, that is, 5, 10 and 15 years. Keywords: Urban expansion. Simulation of scenarios. Cellular automata. RESUMO A urbanização alavancou uma série de problemas nas cidades de médio e grande porte, resultado da falta de planejamento e de tecnologias para apoiar a tomada de decisões. Neste sentido, este trabalho tem como objetivo contribuir para a metodologia de modelagem por autômatos celulares, visando o estudo dos processos que condicionam a expansão da mancha urbana. Tendo como estudo de caso o município de Novo Hamburgo, RS. Para tanto foram utilizadas as manchas urbana de 1967, 1977, 1987, 1997, 2009 e 2015, totalizando uma análise histórica de 48 anos, além dos mapas temáticos: Declividades, Hipsométrico, Uso do Solo, Recursos Hídricos e Sistema Viário. Os dados compilados foram inseridos no ambiente da plataforma Dinamica EGO, que é um software livre que utiliza o sistema de Autômatos Celulares. O software, emprega um conjunto de mapas de entrada, composto por uma paisagem inicial, uma paisagem final e um compilado de variáveis temáticas que são combinadas a partir da definição de pesos de evidência visando gerar os mapas de probabilidade de transição. Os resultados apresentaram índices de similaridade superior 0,9 para as três primeiras modelagem 1977, 1987 e 1997, além de 0,83 para a simulação de 2015. Também foi possível analisar os fatores predominantes para cada processo de expansão, além da simulação de manchas de prognóstico para curto e médio prazo, ou seja 5, 10 e 15 anos. Palavras-chave: Expansão urbana. Simulação de cenários. Autômatos celulares.